Ren-Shen-Bu-Qi decoction alleviates exercise fatigue through activating PI3K/AKT/Nrf2 pathway in mice - Yangyang Chen; Tinghui Gao; Jing Bai; Wenjing Zhang; Yutong Zhou; Ruichang Zhao; Youhui Deng; Xiaogang Liu; Zhangjun Huang; Songtao Wang; Caihong Shen; Sijing Liu; et al. (BMC, 2024)
Abstract Background Fatigue is a prevalent issue that can lead individuals to a sub-health condition, impacting their work efficiency and quality of life. There are limited effective treatment options available for fatigue. Ren-Shen-Bu-Qi decoction (RSBQD) is a proprietary herbal remedy that is designed to address fatigue. However, the specific pharmacological mechanisms and basis of RSBQD are not yet fully understood. Purpose This study aimed to investigate the pharmacological effects and mechanisms of RSBQD in a mouse model of exercise fatigue. Materials and methods UPLC-Q-Orbitrap HRMS was used to analyze the chemical composition of RSBQD. The pharmacological basis and molecular mechanism of RSBQD on exercise fatigue were predicted using network pharmacology analysis. Subsequently, an exercise fatigue mouse model was established and used to analysis the effects of RSBQD. The potential mechanisms were verified by hematoxylin-eosin (HE) staining, real-time fluorescence quantitative PCR (RT-qPCR), Western blot (WB) and molecular docking. Results The results showed that 88 main components of RSBQD were identified, which have mainly belonged to flavonoids and carboxylic acid compounds. The network pharmacology analysis indicated that RSBQD ameliorate fatigue through PI3K/AKT signaling pathway. Notably, RSBQD prolonged the swimming time and diminished body weight loss of exercise fatigue mice (P < 0.05). Meanwhile, RSBQD significantly alleviated the injury of liver and kidney induced by exhaustive exercise, and decreasing the serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea and BUN levels (P < 0.05). In addition, RSBQD was found could relieve exercise fatigue by decreasing the content of creatine kinase (CK), lactate dehydrogenase (LDH), and lactic acid (LA), but increasing the blood glucose (GLU) and liver glycogen (HG) levels (P < 0.05). RSBQD also significantly increased the hepatic superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) but decreased hepatic malondialdehyde (MDA) levels. Moreover, RSBQD was able to upregulate protein level of activated Nrf2 and PI3K/AKT signaling pathways. Conclusions RSBQD mitigates exercise fatigue by reversing metabolic changes and reducing oxidative damage through the PI3K/AKT/Nrf2 signaling pathway. This study offers pharmacological support for the utilization of RSBQD in exercise fatigue treatment. Graphical Abstract